2017
DOI: 10.1016/j.gca.2017.01.013
|View full text |Cite|
|
Sign up to set email alerts
|

Highlighting the wide variability in arsenic speciation in wetlands: A new insight into the control of the behavior of arsenic

Abstract: Highlighting the wide variability in arsenic speciation in wetlands: a new insight into the control of the behavior of arsenic. Geochimica et Cosmochimica Acta, Elsevier, 2017, 203, pp.284-302 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 91 publications
2
37
0
Order By: Relevance
“…The highest As concentrations (1.36±0.34 g L -1 ) were found in the Nabileque river, the only one that has its source in the alluvial plain. In this environment, during the high water levels, anaerobic conditions favor the reductive dissolution of wetland-soil Fe-oxihydroxides and associated elements, such as arsenic and organic matter (Guénet et al, 2017). Such a process could be responsible for the slightly higher As concentration observed in the Nabileque river.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest As concentrations (1.36±0.34 g L -1 ) were found in the Nabileque river, the only one that has its source in the alluvial plain. In this environment, during the high water levels, anaerobic conditions favor the reductive dissolution of wetland-soil Fe-oxihydroxides and associated elements, such as arsenic and organic matter (Guénet et al, 2017). Such a process could be responsible for the slightly higher As concentration observed in the Nabileque river.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, despite the presence of high arsenic content in the shallow perched water-table and the surface water of Nhecolândia, the most alkaline region of the Pantanal, no study has been directed towards a possible release of arsenic from the wetland towards the main draining rivers. The potential release mainly depends on both, the fate of As during the reduction and trapping mechanisms that favor As stabilization in the wetland (Guénet et al, 2017), and the behavior of arsenic during the re-oxidation process occurring at the wetland-river interface (Pédrot et al, 2015). In this framework, the objective of this study is double: first, to identify, among the rivers on the uplands, the possible sources for the high arsenic contents observed in the floodplain and to verify if the floodplain is releasing arsenic to the nearby river network, according to the hydrological connectivity between the wetland and the main draining rivers; second, to verify whether arsenic occurrence detected in an alkaline soil system of Nhecolândia is related to local or regional processes and to identify the factors responsible for these high arsenic contents.…”
mentioning
confidence: 99%
“…50,51 Fh-NP appear when the Fe/OC ratio sufficiently increases (typically above 0.02) 10 and the Fh/oligomer ratio increases with Fe/OC. 10,11,13,42 However, Chen et al 11 did not observe anymore oligomer for Fe/OC ≥ 0.3, while Guénet et al 13,42 report the coexistence of oligomers and ferrihydrite for Fe/OC ≥ 0.4. This discrepancy may be explained by the references used by Chen et al 11 to perform EXAFS linear combination fits which include a ferrihydrite-free Fe(III)-organo-complex reference.…”
Section: Resultsmentioning
confidence: 98%
“…The Cpt-2 signal can thus be assigned to an overall signal for oligomers of Fe octahedra bound to HA via carboxylic groups as predicted by Catrouillet et al 23 The Fe-C distance corresponds to the distances reported in the literature for both natural and synthetic systems. 4,8,9,10,13,42,43 Short and long Fe-Fe distances correspond to edge and single corner sharing Fe octahedra, respectively. 44 Thus, according to the number and distance of the neighbours, the overall average signal could be described as a tetramer formed by two edge sharing dimers in which each octahedron is bound by its upper corner to an octahedron of the second dimer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation